2011
DOI: 10.1016/j.juro.2011.03.162
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Renal Oxygenation During Partial Nephrectomy Using Hyperspectral Imaging

Abstract: Hyperspectral imaging is a real-time noninvasive method to assess renal oxyhemoglobin saturation intraoperatively throughout the kidney. A nadir percent of oxyhemoglobin is attained within 10 minutes of hilar occlusion. This knowledge may allow future surgical or pharmacological interventions that titrate or minimize ischemic injury in real time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…These results corroborate an earlier study performed by Holzer et al 32 Though the normothermic renal oxygenation measurements were further from baseline measurements than the hypothermic renal oxygenation measurements post-reperfusion, there was no statistical difference between the baseline renal oxygenation values and the reperfused renal oxygenation values. These findings support the clinical practice of maintaining donor kidneys on ice in the window before and during the transplant operation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results corroborate an earlier study performed by Holzer et al 32 Though the normothermic renal oxygenation measurements were further from baseline measurements than the hypothermic renal oxygenation measurements post-reperfusion, there was no statistical difference between the baseline renal oxygenation values and the reperfused renal oxygenation values. These findings support the clinical practice of maintaining donor kidneys on ice in the window before and during the transplant operation.…”
Section: Discussionsupporting
confidence: 92%
“…13 Zuzak and coworkers 30,31 have monitored tissue oxygenation intraoperatively with a DLP® hyperspectral imaging system, at near-video frame rates, to study the effects of artery-only clamping and ice slush application on renal oxygenation. 32 Their results indicated that artery-only clamping and 7-10 min of ice slush application can help to minimize the decrease in renal oxygenation during partial nephrectomies. In this pilot study on renal ischemia, we utilized hyperspectral imaging, specifically a visible reflectance imaging system (VRIS), to examine renal parenchyma oxygenation during 30 min of normothermic and hypothermic ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works in this field evaluated tissue perfusion of in vivo perfused kidneys and proposed HSI for postoperative assessment Tracy et al, 2010;Holzer et al, 2011;Zuzak et al, 2011;Crane et al, 2008). In addition to the characterization of water-enriched tissue around 970 nm, the analysis of lipid-sensitive regions in the spectral NIR band might be interesting for the correlation with ischemic injury (van Veen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the previously described DLP®-HSI system for open surgery 8,10,11 , the illumination source is a 500 W Xenon arc lamp. Broadband white light from the source is diffracted and directed to a digital micromirror device (DMD; Texas Instruments, Dallas, TX) ( Figure 2).…”
Section: I) Study Proceduresmentioning
confidence: 99%
“…Holzer et al recently reported the first clinical characterization of the renal response to ischemia in real time using digital light processing hyperspectral imaging (DLP®-HSI) 8 . By incorporating a DLP®-based Agile Light source (OL 490, Optronic Laboratories, Orlando, FL), a conventional laparoscopic light guide, a 0 0 laparoscope, and a customized digital charge-coupled display (CCD) camera (DVC, Austin, TX), we adapted DLP®-HSI for use during laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%